Evaluation of Oat (Avena sativa L.) Genotypes for Yield and Some Quality Parameters in Trakya-Marmara Region - Turhan Kahraman; Asiye Seis Subaşı; Özge Yıldız; Ceylan Büyükkileci; Turgay Sanal (Turkish Journal of Agriculture: Food Science and Technology, 2019)
This study was carried out in 2015-2016 cropping year in Kırklareli ve Edirne locations with 60 oat lines and 4 varieties of commercials (Kırklar, Kahraman, Yeniçeri and Sebat). The experiment was arranged in an alpha lattice experiment design (8 x 8= 64) with three replications. In the research, it was aimed to determine genotypes suitable for the region by examining yield and some quality parameter performances of oat genotypes.The traits such as grain yield (GY), thousand kernel weight (TKW), test weight (TW), plumpness (P, sieved 2.2 mm slotted), husk rate (HR), full grain oat protein (FGOP), starch (S), β-glucan (β-G) and L value (L) content of genotypes were investigated. The variation among oat lines for grain yield was significant and differences for TKW, TW, P, HR, FGOP, S, β-G, and LBV were also determined. The GY, TKW, TW, P, HR, FGOP, S, β-G and LBV of oat lines ranged between 588.3-860.8 (735.0) kg/da, 21.1-44.0 (31.9) g, 49.3-58.9 (54.7) kg/hl, 13.5-93.5 (69.9) %, 12.1-31.1 (23.9) %, 14.9-20.9 (18.1) %, 51.3-60.5 (56.2) %, 3.2-4.7 (4.0) % and 83.6-89.3 (87.1) in Kırklareli and 472.8-90.35 (681.3) kg/da, 23.0-41.3 (32.4) g, 42.9-55.3 (549.2) kg/hl, 22.4-95.8 (74.7) %, 18.3-30.8 (25.0) %, 14.9-20.3 (18.1) %, 53.1-62.8 (57.5) %, 2.9-5.0 (3.9) % and 84.2-89.9 (87.7) in Edirne respectively.The oat lines 14, 16, 19, 43, 3, 48 and Kırklar and Kahraman varieties were hopeful in Kırklareli and the oat lines 16,18,19, 21, 22, 44, 2, 51, 52 and Kahraman variety were hopeful in Edirne location for grain yield and investigated quality parameters. The oat lines 14, 16, 19, 21 and Kahraman variety were suitable in terms of investigated traits in Trakya-Marmara region.